NASAL POLYPS PATHOPHYSIOLOGY, DIAGNOSIS, ANDEMERGING TREATMENTS - Arifullah; Sayyed Muddasir Shah; Muhammand Hafeez; Abdul Samad; Tanveer (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Nasal polyps are tumour like swellings originating from the mucous membrane liningeither the nasal cavity or the paranasal sinuses and is related to chronic rhinosinusitis and asthma .Namely, these polyps can lead to considerable NAO, hyposmia, and recurrent infection, which affectthe patients’ quality of life.Objectives: To develop a treatment outcome assessment tool for evaluating nasosinus polyp patientswith the objective of comparing the efficacy of nasosinus polyp and emerging treatment options withregards to polyp size and its effect towards symptoms.Study design: A Cross sectional study.Place and duration of study . department of ENT kabir medical college from july 2021 to dec 2021Methods: An observational study was performed cross-sectional including 150 patients diagnosedwith nasal polyps. All of them received corticosteroids, biologics or surgical therapy. Stones’ sizechange, as well as the symptom recurrence rate at the initial and after six months to the therapy wereconsidered on the outcomes.Results: When analyzing the results of treatment carried out in 150 patients of the study, lower polypsize reduction was revealed in patients who received biologic agents with the mean decrease of 50%(p < 0. 001, SD = 7. 5). Corticosteroid group was numerically less with 35 % (p < 0. 05, SD = 6. 8)and surgery group was 45 % less (p < 0. 001, SD = 7. 0). The global symptom rating also droppedacross all the groups and this was highly evident in the biologic using groups.Conclusion: Recent intervention therapies especially biologic agents have received a lot of credit inmanaging polyps and alleviating the symptoms. These directive findings endorse the undisputable useand fashioning of biologics in the management of nasal polyps.